Blender 2D animation : the complete guide to the Grease pencil - Blain, John M., 1942- ([Place of publication not identified] : A K Peters/CRC Press, 2021)
This book describes how to access the Grease Pencil component in Blenderand create 2D Animation within the Blender 3D environment. It is assumed that the reader has no previous knowledge of the Blender program and treats 2D Animation using the Grease Pencil as a standalone application. Grease Pencil is a component of the 3D modeling and animation program, Blender. Blender is a free open-source 3D Computer Graphics software toolset used for creating animated films, visual effects, art, 3D printed models, motion graphics, interactive 3D applications, virtual reality and computer games. Key Features: The first comprehensive beginner's guide to the Grease Pencil component of Blender Facets of operation are explained in short concise chapters with cross references Written instruction is accompanied by diagram illustrations in reference to the program's Graphical User Interface The book is also available in a discounted set along with The Complete Guide to Blender Graphics: Computer Modeling & Animation.
IntroductionPreambleDownload & Install BlenderStarting the Blender ProgramThe Graphical User Interface1.1 The Graphical User Interface (GUI)1.2 EditorsThe 3D Gui Diagram1.3 The 3D Animation Workspace1.4 Drawing with the Grease Pencil1.5 The Grease Pencil1.6 Hiding Annotations1.7 The Transition to 2D DrawingThe 2D GUI Diagram1.8 Changing to the 2D Animation Workspace1.9 The 2D Animation Workspace1.10 The 2D Viewport Editor1.11 Editor Controls - Buttons, Icons and SlidersDrawing Strokes2.1 Drawing a Stroke2.2 Drawing a Stroke (Continued)2.3 Erasing Strokes2.4 Stroke Lines and Fill2.5 Stroke Colors - Material Color Mode2.6 Stroke Colors - Vertex Color Mode2.7 Mixing Colors2.8 Texture Strokes2.9 Stroke Color Workspace2.10 Tinting Strokes2.11 New Stroke TypesStrokes Tools3.1 The Tool Panel3.2 The Fill Tool3.3 The Cutter Tool3.4 The Eyedropper Tool3.5 The Line Tool3.6 The Polyline Tool3.7 The Arc Tool3.8 The Curve Tool3.9 The Box Tool3.10 The Circle ToolStrokes Brushes4.1 Brush Type4.2 Brush Types4.3 Adding New Brush Types4.4 Customising a Brush Type4.5 Downloading and Appending BrushesUsing a Drawing Tablet5.1 Emulating a Three Button Mouse5.2 Blender Preferences Editor5.3 2D Viewport Editor Controls5.4 Tablet Properties5.4 Wacom Intous 3D Table PropertiesThe Canvas Explained6.1 The Canvas6.2 The Canvas - Another way6.3 Renaming and Adding Layers6.4 Adding Preconstructed Strokes6.5 Appending Strokes6.6 Using Appended Stroke Types6.7 Browse Material to be Linked6.8 Adding 3D Objects6.9 Adding a Canvas6.10 The Canvas GridStroke Placement7.1 Placing Strokes7.2 2D Viewport Header Stroke Placement Controls7.3 Object Origin7.4 Origin: Stroke Placement7.5 3D Cursor: Stroke Placement7.6 Surface: Stroke Placement7.7 Stroke: Stroke Placement7.8 Aligning and Locking Strokes7.9 Drawing GuidesBackground Image Tracing8.1 Tracing8.2 Drag and Drop Method8.3 Add Image Method8.4 The File browser Editor8.5 TracingSmoothing and Editing Strokes9.1 Editing Strokes9.2 2D Viewport Editor Modes9.3 Editing in Object Mode9.4 Editing in Edit Mode9.5 Proportional Editing9.6 Edit Mode Manipulation Tools9.7 Edit Mode Editing Tools9.8 Editing in Sculpt Mode9.9 Editing with ModifiersStroke Effects10.1 Viewport Shading Options10.2 Stroke Effects10.3 Viewport Display10.4 Flip Effect10.5 Blur Effect10.6 Pixelate10.7 Shadow10.8Wave Distortion10.9 Multiple EffectsAnimating Strokes11.1 Dope Sheet and Timeline Editors11.2 Timeline Animation Play Buttons11.3 Animation Action11.4 Animation Time11.5 Number of Frames11.6 Set up the Scene11.7 Interpolation11.8 Onion Skinning11.9 Timeline Manipulation11.10 Perpetual Motion11.11 Remember the Outliner Editor11.12 The Walk Cycle and Animation11.13 Keyframes and PosingAnimating a Character12.1 The Storyboard12.2 Organising the Outliner Editor12.3 Animating a Character12.4 Movement in the Scene12.5 Walk Cycle Reference Image12.6 Create a Dedicated Sketch Material12.7 Sketching a Pose12.8 Playing the Animation12.9 Scaling and Positioning Keyframes in the Timeline12.10 The Time Offset Modifier.12.11 Animating the Scene Background12.12 Background Image12.13 In PerspectiveArmatures in Animation13.1 The Armature13.2 Multiple Bones13.3 Armature Display13.4 Armature Posing13.5 Parenting with Automatic Weights13.6 Understanding Parenting13.7 Cancel Parenting13.8 Parenting with Envelope Weights13.9 Vertex Groups13.10 Animation KeyframesWrap up and Render14.1 Eevee Render in the Properties Editor14.2 Render Preview14.3 Rendering an Image14.4 Rendering a Video Clip14.5 Video CodecsNavigate and Save15.1 Files and Folders15.2 Creating a Folder15.3 Saving a File15.4 Windows File Explorer15.5 Windows File Explorer Diagram15.6 Blender File Browser15.7 Opening Files15.8 File Browser Header Features15.9 Make a New Folder15.10 Display Options15.11 Saving Your Work15.12 The Concept of Files15.13 The Append or Link Command15.14 Importing ObjectsCreating New Scenes16.1 The Storyboard16.2 Extend the Sequence16.3 Adding a Scene16.4 Create Video ClipsMovie Making17.1 Video Editing Workspace17.2 Placing Files in the VSE17.3 Audio Files - Sound17.4 Precision File Placement17.5 Viewing the Video File17.6 Video File Properties / Modifiers17.7 Erasing (Deleting) a File from the VSE17.8 The Add Button17.9 Cutting Video Strips17.10 Rendering the Movie17.11 SummaryGrease Pencil Modeling18.1 Modeling using the Grease Pencil18.2 Modeling a Stroke18.3 Shaping Strokes18.4 Combining and Converting Strokes18.5 Modeling From Strokes18.6 Modeling Workspace.18.7 Modeling a DragonUsing Add-Ons19.1 Add-ons From the Internet19.2 Download the Add-on19.3 Installing the Python File19.4 Add-on - Another WayInternet ResourcesIndex
OCLC-licensed vendor bibliographic record.
Keywords: Computer animation; Blender (Computer file); Grease pencil; COMPUTERS / Computer Graphics / General; COMPUTERS / Computer Animation; COMPUTERS / Computer Science